2022
DOI: 10.9734/jemt/2022/v28i830426
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Sustainable Procurement in Public Institutions

Abstract: Sustainable procurement has in the recent past generated considerable interest world over considering the potential benefit it presents in preserving the environment and other aspects of human life and development. This is more seemingly been applied more in private firms than in the public sector organisations. The research sought to add to the knowledge of sustainable procurement and how organisations in the public sector can embrace it to facilitate development and service delivery. The research outlined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In purchasing, the role of the supplier and relationship management with the supply base is becoming more recognized. Zambika (2022) emphasized the importance of sustainable procurement, and identified the lack of policy guidelines and top management commitment in the public sector. Moreover, it is found that procurement procedures prioritize financial aspects over non-financial aspects, highlighting the need to balance financial, social, and environmental considerations for sustainable public procurement (Ramadhan and Gomera, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In purchasing, the role of the supplier and relationship management with the supply base is becoming more recognized. Zambika (2022) emphasized the importance of sustainable procurement, and identified the lack of policy guidelines and top management commitment in the public sector. Moreover, it is found that procurement procedures prioritize financial aspects over non-financial aspects, highlighting the need to balance financial, social, and environmental considerations for sustainable public procurement (Ramadhan and Gomera, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable procurement, also known as green procurement or environmental purchasing, is a concept that has gained significant attention in recent years due to its potential benefits in preserving the environment and promoting sustainable development (Zambika, 2022). It involves integrating social, economic, and environmental factors into organisations' procurement processes and procedures (Guandalini, 2022).…”
Section: Introduction 11 Background On Sustainable Procurementmentioning
confidence: 99%
“…In the public sector, sustainable procurement has been less commonly implemented compared to private firms (Zambika, 2022). However, there is a growing recognition of the importance of sustainable procurement in public institutions.…”
Section: Introduction 11 Background On Sustainable Procurementmentioning
confidence: 99%
See 1 more Smart Citation